On the History of Old Believer in Lithuania in 19th Century: Rimkai Old Believer Church Assembly in 1856 and its Resolutions - Morozova, Nadežda (Slavistica Vilnensis, 2021)
The history of Old Believers in Lithuania in the 19th century is insufficiently studied. Well, we know the main centers, events and names of the most important figures, the key moments in the history of the Old Believer society are identified. But there are any generalizing monographs in this field and now the main task is to accumulate empirical material and try to put them in a future common historical narrative. The Old Believer community of Rimkai is one of the oldest in the central part of present-day Lithuania. In 1856 an Old Believers’ church assembly was held in the village of Rimkai. This assembly has so far been unknown in historiography, so this is the first time information about the meeting is being introduced into scientific circulation. The resolutions of the assembly are preserved in the only manuscript, which i s now held at the Russian State Library as part of E. V. Barsov’s collection no. 1025. The resolutions consist of 33 articles discussing the Old Believers’ iconolatry as well as regulation of ritual and everyday norms of behaviour applicable to both church leaders and ordinary parishioners. The documents were signed by 13 Old Believers’ spiritual fathers and monks from Lithuania and East Prussia. This study contains a diplomatic edition of Rimkai resolutions too. The text of the document is supplemented by historical commentary and source analysis.